Treatment and outcomes of high-risk neuroblastoma in Southeast Asia: a single-institution experience and review of the literature - Anselm Chi-Wai Lee; Chan Hon Chui; Robert Kwok; Kim Shang Lee; Chee Meng Fong; Wilfred Hing-Sang Wong (Singapore Medical Journal)
Introduction: In Europe and North America, the majority of children with high-risk neuroblastoma survive the disease. Elsewhere, the treatment outcomes are poor. Methods: A retrospective review of children treated for high-risk neuroblastoma in a single institution in Singapore from 2007 to 2019 was carried out. Treatment consisted of intensive chemotherapy, surgery aimed at gross total resection of residual disease after chemotherapy, consolidation with high-dose therapy followed by autologous stem cell rescue, and radiotherapy to the primary and metastatic sites followed by maintenance treatment with either cis-retinoic acid or anti-disialoganglioside monoclonal antibody therapy. Survival data were examined on certain clinical and laboratory factors. Results: There were 57 children (32 male) treated for high-risk neuroblastoma. Their mean age was 3.9 (range 0.7–14.9) years. The median follow-up time was 5.5 (range 1.8–13.0) years for the surviving patients. There were 31 survivors, with 27 patients surviving in first remission, and the five-year overall survival and event-free survival rates were 52.5% and 47.4%, respectively. On log-rank testing, only the group of 17 patients who were exclusively treated at our centre had a survival advantage. Their five-year overall survival rate compared to patients whose initial chemotherapy was done elsewhere was 81.6% versus 41.1% (P = 0.011), and that of event-free survival was 69.7% versus 36.1% (P = 0.032). Published treatment results were obtained from four countries in Southeast Asia with five-year overall survival rates from 13.5% to 28.2%. Conclusion: Intensified medical and surgical treatment for high-risk neuroblastoma proved to be effective, with superior survival rates compared to previous data from Southeast Asia.